2015
DOI: 10.2214/ajr.14.13804
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Internal Mammary Adenopathy in Patients With Breast Cancer by PET/CT and MRI

Abstract: OBJECTIVE The purpose of this study was to assess the prevalence of internal mammary node (IMN) adenopathy in patients with breast cancer and compare breast MRI and PET/CT for detection of IMN adenopathy. MATERIALS AND METHODS This retrospective study included 90 women who underwent MRI and PET/CT before neoadjuvant chemotherapy for clinical stage IIA through IIIA disease. MRI and PET/CT examinations were read independently by two readers trained in breast imaging and nuclear medicine. All patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
(31 reference statements)
0
26
0
Order By: Relevance
“…The EQD2 > 63. 5 Gy was associated with improved DFS in patients with IMN size ≥1.0 cm. However, the association between IMN radiation dose and DFS was not significant in patients with IMN size < 1.0 cm.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The EQD2 > 63. 5 Gy was associated with improved DFS in patients with IMN size ≥1.0 cm. However, the association between IMN radiation dose and DFS was not significant in patients with IMN size < 1.0 cm.…”
Section: Discussionmentioning
confidence: 85%
“…Previous surgical studies found that the frequency of pathologic IMN involvement was between 28 and 52% in patients with axillary lymph node (ALN) metastasis, while it was between 5 and 17% for patients without ALN metastasis [2,3]. According to recent studies in which contemporary imaging modalities such as computed tomography (CT), magnetic resonance imaging (MRI) or positron emission tomography-computed tomography (PET-CT) were performed, the incidence of cIMN+ ranged between 11 and 16% in breast cancer patients with advanced nodal disease (cN2-N3) [4,5]. Even though cIMN+ is frequently observed in patients with breast cancer, the optimal treatment method and prognosis have not been well identified.…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations for improved overall survival can be the introduction of other systemic regimen, such as trastuzumab, or detecting smaller IMLNMs with SLNB. Nowadays, the size of internal mammary lymph nodes detected using state-of-the-art imaging techniques such as PET/CT and MRI approaches the size of internal mammary nodes visualized during SLNB [1517]. This suggests comparable prognosis of SLNB-detected IMLNMs and imaging-detected IMLNMs.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, there was no distinction in our cohort of pN2b patients detected by for instance physical examination, ultrasound, MRI, or PET-CT. Yet, a previous study of Jochelson et al demonstrated a difference in the prevalence between several imaging techniques for detecting internal mammary adenopathy [17]. …”
Section: Discussionmentioning
confidence: 99%
“…38,42,43 PET and MR imaging have demonstrated similar performance for the detection of internal mammary adenopathy. 44 MR imaging and PET/MR imaging have been shown to be more likely than PET/CT to determine the correct maximum diameter of the tumor (T stage), which may be useful in surgical and oncologic planning. 38 Hybrid PET/MR imaging may be of particular use in this extent-of-disease setting, where the increased sensitivity of MR imaging for multifocal disease and the increased sensitivity of PET for axillary nodal disease could come together in a single examination.…”
Section: Mr Imaging and Pet In Localized Breast Examinationsmentioning
confidence: 99%